Joint preservation in a middle-aged man with knee osteoarthritis, using novel techniques - Seyawash Fooladi; Abhishek Vaish; Yash Nigam; Raju Vaishya (Apollo Medicine)
The incidence of knee osteoarthritis (KOA) is on the rise and is affecting the younger population. The treatment of these younger individuals is challenging, and the treatment strategies should involve techniques to postpone or alleviate the need for joint replacement for these people. Regenerative treatment methods are useful and effective in the management of KOA at an early age. We present a case of a middle-aged man with KOA, who was managed by combined procedures of the proximal fibular osteotomy, microfracture of the cartilage lesion, and bone marrow aspirate concentrate.